Impairment in Sulfite Reductase Leads to Early Leaf Senescence in Tomato Plants. Issue 4 (1st July 2014) - Yarmolinsky, Dmitry; Brychkova, Galina; Kurmanbayeva, Assylay; Bekturova, Aizat; Ventura, Yvonne; Khozin-Goldberg, Inna; Eppel, Amir; Fluhr, Robert; Sagi, Moshe
Abstract : Insufficient sulfite reductase activity activates the upstream components of the sulfate reduction pathway in tomato plants, resulting in accumulation of toxic sulfite and early leaf senescence. Abstract: Sulfite reductase (SiR ) is an essential enzyme of the sulfate assimilation reductive pathway, which catalyzes the reduction of sulfite to sulfide. Here, we show that tomato ( Solanum lycopersicum ) plants with impaired SiR expression due to RNA interference (SIR Ri ) developed early leaf senescence. The visual chlorophyll degradation in leaves of SIR Ri mutants was accompanied by a reduction of maximal quantum yield, as well as accumulation of hydrogen peroxide and malondialdehyde, a product of lipid peroxidation. Interestingly, messenger RNA transcripts and proteins involved in chlorophyll breakdown in the chloroplasts were found to be enhanced in the mutants, while transcripts and their plastidic proteins, functioning in photosystem II, were reduced in these mutants compared with wild-type leaves. As a consequence of SiR impairment, the levels of sulfite, sulfate, and thiosulfate were higher and glutathione levels were lower compared with the wild type. Unexpectedly, in a futile attempt to compensate for the low glutathione, the activity of adenosine-5′-phosphosulfate reductase was enhanced, leading to further sulfite accumulation in SIR Ri plants. Increased sulfite oxidation to sulfate and incorporation of sulfite into sulfoquinovosyl diacylglycerols were not sufficient to maintain low basal sulfite levels, resulting in accumulative leaf damage in mutant leaves. Our results indicate that, in addition to its biosynthetic role, SiR plays an important role in prevention of premature senescence. The higher sulfite is likely the main reason for the initiation of chlorophyll degradation, while the lower glutathione as well as the higher hydrogen peroxide and malondialdehyde additionally contribute to premature senescence in mutant leaves.